O processo de formação de conceitos na perspectiva vigotskiana - Fonseca-Janes, Cristiane Regina Xavier [UNESP]; Lima, Elieuza Aparecida de [UNESP] (My University, 2013)
In his work on human knowledge, Vygotsky reveals the second human nature, the one which is historical and cultural, due to people´s learning throughout life, through the mediation of others and the concrete conditions of life and education. In this eminently social process, the child grows into the intellectual life having the adult as a peer and learns human skills from this adult-child interaction. This means that, for working with abstract formulation, it is necessary understanding it as a complex, dynamic and functional act that is built by the insertion of individual performance into culture that is mediated by interaction with others. In this setting, each individual reaches knowledge through formal and non-formal learning that help on the formulation of scientific and everyday concepts. To make studies on the process of concept formation, Vygotsky adopted an experimental methodology based on the philosophical assumptions of Marxist theory of how mental processes occur, once he perceived these processes in a constantly changing and moving. Thus, the method called “Instrumental, Cultural and Historical” differed from conventional experimental studies focused on the performance of the task itself. The method adopted by Vygotsky was concerned with the process of concept formation and not only with fragmentary cutouts of cognitive processes. According to our study, the formation of the social nature of man develops from processes of appropriation and objectification of knowledge, which makes individual the historically constructed achievements by mankind, as, for example, types of sophisticated thinking, which requires the discussion of concept formation.

Em seus trabalhos sobre o conhecimento humano, Vigotski revela a segunda natureza humana, aquela de cunho histórico-cultural, decorrente de aprendizagens que cada pessoa realiza no decurso de sua vida, por meio da mediação do outro e de condições concretas de vida e de educação. Nesse processo eminentemente social,a criança penetra na vida intelectual da geração adulta e se apropria de capacidades especificamente humanas. Isso significa que, para se trabalhar no plano abstrato,são necessárias formulações de conceitos, entendidos como um ato complexo,dinâmico e interfuncional, construídos por meio da atuação e inserção do indivíduo na cultura, mediado pelas relações com as outras pessoas. Nesse meio, o indivíduorecebe conhecimentos por meio de aprendizados formais e não-formais promotores de subsídios para construção dos conceitos científicos e cotidianos. Para realizar seus estudos sobre o processo de formação de conceitos, Vigotski utilizou um método experimental pautado nos pressupostos filosóficos da teoria marxista do funcionamento dos processos mentais, porque percebia estes processos como em constante mudança e movimento. Assim, o método denominado “Instrumental Cultural e Histórico”diferenciava-se dos estudos experimentais convencionais centrados no desempenho da tarefa em si. O método utilizado por Vigotski preocupava-se com o processo de formação de conceitos e não apenas com recortes estáticos dos processos cognitivos.Depreendemos, em nosso estudo, a constituição da natureza social do homem a partir de processos de apropriação e objetivação de conhecimentos, que torna individuais as conquistas historicamente construídas pela humanidade, dentre as quais tipos sofisticados de pensamento, o que requer discutir a formação de conceitos.
The process of formation of concepts in a Vygotskyan perspective
Keywords: Vigotski; Epistemologia; Formação de Conceitos; Ontogênese